International leadership for the control of disease outbreaks relating to “One Health” - Samlee Plianbangchang (Journal of Health Research, 2018)
Purpose - In view of the current global challenge of infectious diseases transmitted from animal to man, this is a complimentary piece of paper to promote, in particular, the inter-sectorial and multi-disciplinary coordination and cooperation in their prevention and control, among all concerned agencies/organizations at both policy and operational levels, with special emphasis on the importance of leadership development within the socio-cultural context of health, and with particular reference to the concept of “One Health” that implies the intimate interaction between man and animal within their own environments/ecosystems. The paper aims to discuss these issues. Design/methodology/approach - This is a commentary piece. Findings - The paper directly and indirectly suggests lacunae in several areas of concern for further research and development to fill the knowledge gap in such a prevention and control. Originality/value - This is a commentary piece.